The Effect Of Progressive Mobilization On The Event Of Decubitus In Patients With Mechanical Ventilation In Icu Room Of Mangusada Hospital - IGAA Sherlyna Prihandhani; Ni Komang Matalia Gandari; I Dewa Agung Gde Fanji Pradiptha; Nina Rismawati Hakim (Universitas STRADA Indonesia, 2021)
This study aimed at identifying the effect of progressive mobilization on pressure ulcer incidents in patient with mechanical ventilation in the Intensive Care Unit at Mangusada Hospital. The design of this study was PreExperiment (one group pretest and posttest design). The instrument used in this study was a standard procedure of Richmond Agitation Sedation Scale (RASS) and observation sheet of Decubitus. The result of the test indicated most of the respondents experienced grade I pressure ulcer (decubitus) before being given progressive mobilization therapy and after the therapy, all respondents (100%) did not show pressure ulcer (decubitus) incident. Wilcoxon test showed that there was an effect of progressive mobilization on pressure ulcer incidents in patient with mechanical ventilation in the Intensive Care Unit at Mangusada Hospital (p-value = 0,042).